Unusual location of osteochondroma in the temporal region in a patient with functional pituitary adenoma - Henry Olayere Obanife (SAGE Publishing, 2021)
Osteochondromas are common in the long bones and relatively rare in the head and neck regions. We herein report a case of a solitary temporal bone osteochondroma associated with a functional pituitary adenoma hypersecreting prolactin. The patient was a 48-year-old man with progressive, painless temporal swelling associated with gradual visual loss, gynaecomastia, erectile dysfunction, and loss of libido. A brain computed tomography scan with bone windows showed right temporal sessile bony expansion and a pituitary tumour. A pituitary function test revealed hyperprolactinaemia. His symptoms resolved with medical management, and excisional biopsy of the temporal tumour confirmed an osteochondroma. To the best of our knowledge, this is the first reported case of a solitary temporal bone osteochondroma with a functional pituitary adenoma hypersecreting prolactin.